Latent TB infection in solid organ transplant recipients in Serbia: A single center experience from a low TB burden country - Jovana Milisavljevic; Maja Stosic; Nataša Jovanovic; Tatjana Adzic Vukicevic (PLoS ONE, 2026)
Background Solid organ transplant (SOT) recipients face a heightened risk of latent tuberculosis infection (LTBI) reactivation and progression to active tuberculosis (TB) because of their immunosuppressed state . In low TB burden countries like Serbia, data on LTBI and TB incidence in transplant recipients are limited. Objectives To determine the prevalence of latent tuberculosis infection and the incidence of active tuberculosis among kidney and liver transplant recipients, and to identify factors associated with LTBI in this high-risk group. Methods A retrospective cohort study was conducted among 275 adult SOT recipients (203 kidney, 72 liver) who underwent transplantation at a tertiary care center in Serbia between 2007 and 2017. LTBI was assessed using Interferon-Gamma Release Assay. Patients were followed for five years post-transplantation to monitor for LTBI and active TB. Multivariable logistic regression was used to identify independent predictors of LTBI. Results The post-transplant LTBI prevalence among kidney transplant recipients was 23.4 (95% CI = 14.7%–35.1%), while 5.6 (95% CI = 2.2%–13.4%) among liver transplant recipients (p = 0.003). The crude incidence of post-transplant TB was 151.4 per 100,000 person-years, over seven times higher than the general population in Serbia. Median time to TB diagnosis was 6 months (IQR: 3.0–12.0). Independent predictor of LTBI was previous contact with a TB case (OR =26.08; 95% CI = 5.63–120.90). Conclusions The substantially elevated burden of LTBI and TB among SOT recipients underscores the need for systematic LTBI screening and targeted preventive treatment. Strengthened collaboration among transplant physicians, pulmonologists, and public health teams is essential to improve TB prevention strategies in this vulnerable population, particularly in countries aiming for TB elimination.